The association between sarcopenia and clinical outcomes among Chinese patients with triple-negative breast cancer: a retrospective study - Gu, Huayan; Zhu, Teng; Ding, JiaLing; Yang, Zhi; Lu, Yiqiao; Guo, Guilong (Frontiers in Oncology, 2025)
PurposeThis study efforts to explore the association between sarcopenia, an age-related decline in muscle mass and physical function, and clinical outcomes in women with triple-negative breast cancer (TNBC).Methods and materialsThis retrospective study included women diagnosed with TNBC who received breast surgery from December 2012 to December 2018. Skeletal muscle mass index (SMI) is utilized to evaluate sarcopenia, which was quantified by the cross-sectional area of muscle at the twelfth thoracic vertebra (T12). Disease-free survival (DFS) and overall survival (OS) are the endpoints. The association of sarcopenia with DFS and OS was statistically analyzed.ResultsThe study included 130 women in all, with a median age of 55 years (median follow-up, 53 months). Among them, 78 (58.5%) women had sarcopenia (SMI <28.01). 38 patients (29.2%) died and 49 patients (37.7%) experienced a recurrence of breast cancer throughout the follow-up period. Sarcopenia was demonstrated to be a significant predictive factor for both OS (HR,2.885; 95% CI, 1.349–6.169; p = 0.006) and DFS (HR,3.121; 95% CI, 1.578–6.175; p = 0.001) in the multivariate Cox proportional hazard model. There was no significant correlation seen between body mass index and either DFS (p = 0.156) or OS (P = 0.264). Logistic regression model further revealed that sarcopenia was a prognostic factor that was independently associated with both DFS (p = 0.001) and OS (p = 0.006).ConclusionsAmong women with TNBC, sarcopenia is associated with worse clinical outcomes. These patients with high risk might be candidates for individual programmed exercise and diet interventions to optimize survival outcomes.